2016
DOI: 10.1016/j.vaccine.2016.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Post-licensure surveillance of quadrivalent inactivated influenza (IIV4) vaccine in the United States, Vaccine Adverse Event Reporting System (VAERS), July 1, 2013−May 31, 2015

Abstract: BackgroundQuadrivalent inactivated influenza vaccines (IIV4) were first available for use during 2013−14 influenza season for individuals aged ≥6 months. IIV4 is designed to protect against four different flu viruses; two influenza A viruses and two influenza B viruses.MethodsWe searched the Vaccine Adverse Event Reporting System (VAERS) for US reports after IIV4 and trivalent inactivated influenza vaccine (IIV3) from 7/1/2013–5/31/2015. Medical records were requested for non-manufacturer reports classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…The level of detection of AEIs in our pilot study is comparable to that found in other observation systems [ 33 , 34 ]. This seems to suggest that use of ADR cards together with EHR system weekly data extractions is an appropriate tool for adverse event surveillance.…”
Section: Discussionsupporting
confidence: 89%
“…The level of detection of AEIs in our pilot study is comparable to that found in other observation systems [ 33 , 34 ]. This seems to suggest that use of ADR cards together with EHR system weekly data extractions is an appropriate tool for adverse event surveillance.…”
Section: Discussionsupporting
confidence: 89%
“…The safety profile observed for 9vHPV is consistent with data from the vaccine's prelicensure clinical trials and is similar to postlicensure safety monitoring data for 4vHPV and bivalent HPV vaccine and for other vaccines administered in this age group (eg, tetanus, diphtheria, and acellular pertussis; meningococcal conjugate; and influenza vaccines). 7,[36][37][38][39] For 9vHPV, 97.4% of reports to the VAERS were classified as nonserious (versus 94.2% for 4vHPV); crude AE reporting rates for all reports and serious reports were 259 and 7 reports per million doses distributed, respectively (versus 327 and 19 reports per million, respectively, for 4vHPV); and the most frequently reported AEs (dizziness, syncope, headache, nausea, and injection site reactions) were similar to those observed for 4vHPV. 7 VAERS is a critical early warning system to detect possible safety problems in US-licensed vaccines and is a key component of the US vaccine safety monitoring infrastructure.…”
Section: Discussionmentioning
confidence: 80%
“…An investigation on the VAERS reports following vaccination with IIV4 and trivalent IIV3 from 7/1/2013 to 5/31/2015 was conducted by Haber et al., 40 who reported similar safety profiles between the two vaccines. This observation was in agreement with the data obtained from pre-licensure studies of IIV4.…”
Section: Vaccine Types and Production Methodsmentioning
confidence: 99%